Industrial - Qamaruz Zaman, Faridah (Universiti Putra Malaysia Press, 2014)
This chapter challenges the notion of a typical factory. Hidden in the microscopic world, these tiny organisms are manufacturers par excellence of perfumes, medicines, enzymes, and biopolymers. So the next time one injects insulin, or wear an oudh perfume, one should give thanks to these unsung little heroes